Pengembangan Antarmuka Website Kebugaran Fitme untuk Mendukung Pola Hidup Sehat dengan Penerapan Metode Human-Centered Design - Putra, Anak Agung Adi Wiryya; Wanditya, I Made Dedy; Fhadillah, Moh. Lukman Hakim (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2025)
Healthy living is often associated with achieving an ideal body weight, which is the goal of many people who are overweight. Therefore, various methods are carried out to achieve the desired body weight. FitMe is present as a website designed to make it easier for the public to get information related to the importance of maintaining an ideal body weight. FitMe equipped with various features such as personalized workout programs, diet and nutrition monitoring, exercise trackers, daily journal entries, fitness consultation, comprehensive fitness education materials, as well as a marketplace for the purchase of products such as protein milk and nutritious foods. This research uses the Human Centered Design method, which is an approach that focuses on all users, both potential and not. Human Centered Design is determined in this research because this method focuses on a wider range of users. Design testing is carried out using the UEQ method on 20 respondents and the results obtained are Excellent, which means that the design of Fitme has met the user's criteria and there is no need to undergo a redesign process.